IFRS ADOPTION AND PERFORMANCE OF QUOTED CONSUMER GOODS MANUFACTURING COMPANIES IN NIGERIA - ALU, Chituru Nkechinyere; Akinwunmi, Abiodun Jelil (Archives of Business Research, 2017)
Abstract Globalization has generated the need for a world-wide harmonized Standards of Accounting and financial reporting for the benefit of users and preparers of the financial reports. This study seeks to investigate the Adoption of International Financial Reporting Standards (IFRSs)by Nigerian Quoted Consumer Manufacturing Companies with the view of establishing empirically, the appropriateness or otherwise of the adoption. An ex-post-facto research design was adopted for the study. Secondary data were obtained from the audited annual financial reports of ten (10) of such manufacturing companies purposively selected from the population of manufacturing companies listed on the Nigerian stock exchange for a period of five (5) years (2010-2014). The data analysis was done using the pooled OLS estimator through the aid of Stata software version 11. The findings show that there is no significant relationship between the adoption of IFRS and performance of manufacturing firms listed on the Nigerian Stock Exchange. However, the findings of this study might be affected by the choice of accounting policies of the companies under investigation and some environmental factors such as the economic, socio-cultural, political and legal factors. Hence, one can therefore assert that, although the adoption of IFRS is not significantly related to the performance of Quoted Consumer Manufacturing Companies, Nigerian companies’ adoption of IFRS is worthwhile in view of the fact that it enhances better accountability, comparability, transparency and as well, improves the quality of financial reporting, however, IFRS is not an end in itself but a means to an end.